Efforts to Improve Teacher Performance through Pedagogical Competence and Work Motivation at Global Insani Islamic School - Nurhasanah, Anah; Ratnaningsih, Sita (Jurnal Inovasi Pendidikan MH Thamrin, 2026)
Schools are one of the educational institutions that can be considered a vehicle for achieving Indonesia's goals of independence. The success of these goals depends on the human resources within the school, including the principal, teachers, students, and other educational staff. Teachers are one of the components that determine the implementation of the educational process. The teacher is the main actor as a facilitator in organizing the student learning process. Therefore, teacher performance is very influential in realizing national education programs. Teachers must have sufficient quality, because teachers are one of the micro compone~nts of the education system which is very strategic and plays many roles in the educational process. This research aims to determine efforts to improve teacher performance through pedagogical competence and work motivation. This research was carried out using a qualitative approach, by conducting interviews and observations to determine the extent to which pedagogical competence and work motivation can improve teacher performance. From the results of the research conducted, it can be concluded that teachers who have good pedagogical competence can provide learning to students according to their needs, so that they can improve their performance. Like wise with the teacher's work motivation, the higher the teacher's work motivation, the greater the teacher's performance. This is an effective effort to improve teacher performance. Thus increasing pedagogical competence and work motivation can improve teacher performance.